2018
DOI: 10.1002/ptr.6119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oligomeric grape seed proanthocyanidins on L‐NAMEinduced hypertension in pregnant mice: Role of oxidative stress and endothelial dysfunction

Abstract: The aim of this study was to investigate the effects of Grape Seed Proanthocyanidins (GSP) on Nω-Nitro-L-arginine methyl ester-induced hypertension in pregnant mice. Fifty Kunming mice were randomized into control, control + GSP, model, and model + GSP. Three weeks later, the artery systolic blood pressure was examined and the related pathological changes were detected. Aorta relaxation function was assessed by aorta ring apparatus. Blood urea nitrogen and serum creatinine were measured by an automatic biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
2
6
1
Order By: Relevance
“…However, in addition to placental oxidative stress and impaired placental function ( Myatt and Cui, 2004 ; Burton, 2009 ), an excessive production of ROS has been associated with the pathophysiology of many maternal hypertensive pregnancy-related complications, such as PE ( Myatt and Cui, 2004 ; Burton and Jauniaux, 2011 ; Matsubara et al, 2015 ; Chiarello et al, 2020 ; San Juan-Reyes et al, 2020 ). In agreement with recently published data in the L-NAME mouse model ( Zhu et al, 2018 ), we found that circulating concentrations of MDA were increased in the maternal plasma of eNOS –/– mice compared with WT control groups, and that treatment with GSEP significantly reduced this marker of lipid peroxidation in the hypertensive strain. One significant limitation of this study is mouse plasma volume availability, as investigation of several relevant biomarkers in addition to MDA, are needed to address a complete evaluation of oxidative stress in both maternal and fetal samples.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, in addition to placental oxidative stress and impaired placental function ( Myatt and Cui, 2004 ; Burton, 2009 ), an excessive production of ROS has been associated with the pathophysiology of many maternal hypertensive pregnancy-related complications, such as PE ( Myatt and Cui, 2004 ; Burton and Jauniaux, 2011 ; Matsubara et al, 2015 ; Chiarello et al, 2020 ; San Juan-Reyes et al, 2020 ). In agreement with recently published data in the L-NAME mouse model ( Zhu et al, 2018 ), we found that circulating concentrations of MDA were increased in the maternal plasma of eNOS –/– mice compared with WT control groups, and that treatment with GSEP significantly reduced this marker of lipid peroxidation in the hypertensive strain. One significant limitation of this study is mouse plasma volume availability, as investigation of several relevant biomarkers in addition to MDA, are needed to address a complete evaluation of oxidative stress in both maternal and fetal samples.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, a previous preclinical study investigated the effect of intragastric administration of GSEP in pregnancy, using the L-NAME-induced hypertensive mouse model. The authors measured SBP under anesthesia and demonstrated that treatment with GSEP reversed the hypertensive effect induced by L-NAME after 3 weeks of intervention (Zhu et al, 2018). In agreement with this finding, the current study showed a significant blood pressure-lowering effect of maternal supplementation with GSEP in pregnant eNOS −/− mice.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations